BIOACTIVATORS EFFECTIVENESS AND UTILIZATION IN BULKING AGENTS OF WATER HYACINTH AS COMPOST - Firda Herlina (Fakultas teknik Universitas Muhammadiyah Jakarta, 2014)
Water hyacinth is a water plant species of the most dominating in the waters –waters or rivers - rivers. Water hyacinth has the ability to multiply very quickly that in aninstant the surface waters can be closed by the presence of water hyacinth. Researchshows that the extent of cover of water hyacinth is now more widely because of the abilityof growing 2.6 times faster in open water. This can be overcome by using water hyacinthand processes it into compost, because the water hyacinth contains a very high watercontent of 96%, then to reduce the water content is added bulking agent and to acceleratethe composting process that is able to degrade added bioactivator water hyacinth.In this study the materials used are water hyacinth, and as a bulking agent iszeolite, bentonite, sawdust. Then the water hyacinth and bulking agent are mixed, thenaddedbioactivator Primadek, EM4 and, on each - each treatment. The composting processusing aerobic composter. The composting process is stopped when the C / N ratio hasreached the limit required by the SNI Compost (10-20). This process is conducted in adevice called a composter.The results showed that, for the treatment of water hyacinth with zeolite andcompostEM4 mature at day 14, water hyacinth with bentonite and EM4 pda day 15. In general,the resulting compost compost quality standards (SNI 19-7030-2004), unless the ratio ofC / N for EG + SG + EM4 newly reached 43.88. Based on the results of VarianceAnalysis (Anova) followed by DMRT showed that the addition of bulking agent and fortreatment bioactivator + Z + EM4 EG and EG + B + EM4 significantly different in C / Nratio of compost but not significantly different in content of nitrogen (N), phosphorus (P)and potassium (K).